Novel evaluation method for densitometric curves of von Willebrand Factor multimers and a new parameter (MMW) to describe the degree of multimersation - Udvardy, Miklós L.; Szekeres-Csiki, Katalin; Hársfalvi, Jolán (Thrombosis and Haemostasis, 2009)
Von Willebrand factor (VWF) is built up from a varying number of subunits, of which the larger molecules have higher haemostatic activity. Von Willebrand disease (VWD) and thrombotic thrombocytopenic purpura are the best known disorders with pathognomonic changes of the highly multimerised VWF forms. There is an established method to calculate the relative amount of large oligomers. Our aim is to quantify the degree of VWF multimerisation as well, to complete the densitometric analysis of VWF electrophoresis. After optimisation, we have defined this new parameter (MMW) as the molecular weight corresponding to the lower boundary of the largest 25% of VWF protein. MMW was significantly different (p<.0001) in platelet lysate, normal samples and VWD type 2 samples (10.4, 6.3, 2.1, respectively). There was strong correlation between the MMW and the amount of large multimers in normal samples (r2=0.98) and in platelet lysate. However MMW was higher in latelet lysate, in which VWF is not cleaved by ADAMTS-13, than in healthy samples with the same amount of large multimers. Comparison of the new parameter and the collagen binding and ristocetin cofactor activity of VWF, showed that the functional tests are at least partially determined by the multimerisation; however, about 15% of VWD samples had normal activity to antigen ratios. The quantification of multimerisation aids the classification in these cases, especially at low antigen concentrations, and also might help in the detection of thrombotic conditions.
Keywords: VWF multimer analysis; von Willebrand disease